Industrial experience with building a web portal product line using a lightweight, reactive approach. - Pettersson, Ulf (Software engineering notes.)
Imprecise, frequently changing requirements and short time-to-market create challenges for application of conventional software methods in Web Portal engineering. To address these challenges, ST Electronics (Info-Software Systems) Pte. Ltd. applied a lightweight, reactive approach to support a Web Portal product line. Unique characteristics of the approach were fast, low-cost migration from a single conventional Web Portal towards a reusable "generic Web Portal" solution, effective handling of large number of functional variants and their dependencies, the ability to rapidly develop new Web Portals from the generic one, and to independently evolve multiple Web Portals without ever losing a connection between them and the "generic Web Portal". The initial Web Portal was built using state-of-the-art conventional methods. The Web Portal was not flexible enough to reap the benefits of new business opportunities that required the company to rapidly develop and further maintain many similar Web Portals. To overcome the limitations of the conventional solution, a reuse technique called XVCL was applied incrementally. Over a period of three weeks, the conventional solution was converted into a Web architecture capable of handling nine Web Portals from a base of code smaller than the original Web Portal. In the paper, we describe the process that led to building the above Web Portal product line. We explain the difficulties in building an effective generic Web solution using conventional techniques. We analyze our reuse-based solution in qualitative and quantitative ways.